Special Al-MOF / polysiloxane composite impregnating compound for basalt fiber and preparation method of special Al-MOF / polysiloxane composite impregnating compound

Through the application of Al-MOF/polysiloxane composite wetting agent, the problem of improving the thermal mechanical properties and wetting properties of basalt fibers is solved, and the stable performance and surface double-sparing properties of the fibers at high temperatures are achieved. It is suitable for special-purpose clothing and The field of thermal filtering devices.

CN119263653APending Publication Date: 2025-01-07QINGDAO UNIV

Patent Information

Application Number
CN202411379782.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing basalt fiber wetting agents are difficult to effectively improve their thermomechanical and wetting properties, especially under high temperature conditions, and the traditional wetting agents are complex in composition, which increases the difficulty of developing new wetting agent systems.

Method used

Al-MOF/polysiloxane composite wetting agent is used to prepare Al-MOF nanoparticles through hydrothermal reaction, and combine with water-based polysiloxane to form a water-soluble composite wetting agent. It is applied to the surface of basalt fibers through ultrasonic dispersion technology. Form a variety of interaction forces such as covalent bonds and hydrogen bonds to improve fiber performance.

Benefits of technology

Thermomechanical and wetting properties of basalt fibers are significantly improved. The tensile fracture stress of the fiber is maintained at 250℃ and the strength is maintained at 85% at 400℃, achieving double-spray-anti-fouling and waterproofing properties of hydrophobic oleophobic , suitable for high temperature resistance, anti-fouling and waterproof self-cleaning functions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263653A_ABST
    Figure CN119263653A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fiber impregnating compounds, and relates to an Al-MOF / polysiloxane composite impregnating compound special for basalt fiber and a preparation method thereof.The preparation method comprises the steps that an ethanol water solution serves as a solvent, Al-MOF nanoparticles are added, ultrasonic dispersion is conducted, and Al-MOF suspension liquid is prepared; adding a water-based polysiloxane solution into the Al-MOF suspension, and carrying out ultrasonic dispersion, so as to obtain the special Al-MOF / polysiloxane composite impregnating compound for the basalt fibers; the preparation method is scientific in principle, simple to operate, efficient, low in cost, few in components and simple in sizing process. After the basalt fiber is subjected to sizing treatment through the impregnating compound, a topological structure similar to basalt components can be constructed on the surface of the basalt fiber, the fiber is endowed with excellent thermal mechanical performance and surface amphiphobic performance, and the high-temperature-resistant, anti-pollution, waterproof and self-cleaning functions of the textile type basalt fiber in the fields of special-purpose clothes and hot filtering devices can be achieved. The method has great application potential and is suitable for large-scale popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the technical field of fiber sizing agents, and relates to a special textile sizing agent for basalt fiber and a preparation process thereof, in particular to an Al-MOF / polysiloxane composite sizing agent for improving the thermomechanical properties and wetting properties of basalt fiber and a preparation method thereof. Background technology:

[0002] Basalt fibers (BFs) are known for their excellent mechanical properties, heat resistance and environmental protection characteristics. They are widely used in fire-resistant and heat-resistant clothing or heat-resistant filter devices to ensure their strong mechanical properties under high temperature conditions. Commercial basalt continuous fiber filaments are almost composed of non-metallic (Si, O) and metallic (Al, Fe, Na, Ca, Mg, K, Ti, Mn) elements and some other trace elements that may come from the environment. For BFs with a certain composition, scratches, crystal defects and void defects may exist during the fiber production process, resulting in a decrease in its performance. The common method to solve this problem is to apply a wetting agent on its surface. The wetting agent plays a role in bundling, cooling, lubrication and interface enhancement during the production of basalt fibers. However, the composition of traditional wetting agents is relatively complex, including wetting agents, coupling agents, antistatic agents, lubricants, etc., which also increases the difficulty of developing new wetting agent systems. In recent years, although great progress has been made in the research of BFs impregnant systems, most of them are used for GFs or CFs. Improper selection of impregnants will seriously affect the performance of BFs intrinsic properties. Therefore, it is urgent to solve the problem of developing a special impregnant system for continuous BFs.

[0003] The Chinese patent "High-temperature resistant basalt fiber composite material and its preparation method" (CN117659706A) discloses a basalt fiber / polysiloxane resin composite material resistant to high temperatures of 600°C. The high-temperature resistant basalt fiber composite material includes the following raw materials by weight: 60-80 parts of basalt fiber, 20-30 parts of polysiloxane resin, and 1-5 parts of curing agent. The preparation method includes: mixing the prepared polysiloxane resin and curing agent, uniformly coating them on the basalt fiber to prepare a prepreg; cutting and flattening the prepreg, pre-curing it by a molding process, and post-curing the molded composite material in an oven. Here, the polysiloxane resin is used as an adhesive and also has the function of a resin matrix. A curing agent needs to be added to initiate a curing reaction to give the entire composite material high-temperature resistance. Moreover, the patent uses short basalt fiber filaments, and does not involve the surface treatment of continuous basalt fiber filaments, let alone the improvement of the fiber surface wettability. The Chinese patent "A reinforced basalt fiber sizing agent and its preparation method" (CN113480199A) mainly consists of epoxy resin and double-layer microcapsule particles, in which Al-MOF exists in the double-layer microcapsule particles, which can repair basalt fibers at room temperature and improve mechanical properties at room temperature, but it does not mention the improvement of temperature resistance and wetting performance. Patent CN111153608A discloses an organic / inorganic hybrid film-forming, microcapsule-type high-temperature self-repairing basalt fiber sizing agent and its preparation method. The sizing agent includes methylphenyl silicone resin emulsion, low-temperature melting glass powder, etc. The low-temperature melting glass powder is used as the core material and the silicone resin is used as the wall material. It can repair cracks in basalt fibers at working temperatures above 400°C and improve mechanical properties. The patent focuses mainly on the self-repairing properties of basalt fibers under high temperature conditions, but does not focus on the improvement of the thermomechanical properties of the fiber itself and the surface wetting properties, and the system is relatively complex. Summary of the invention:

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an Al-MOF / polysiloxane composite wetting agent for improving the thermomechanical properties and wetting properties of basalt fiber and a preparation method thereof. The wetting agent system only comprises two components, Al-MOF and water-based polysiloxane. Al-MOF refers to aluminum-based metal organic framework materials such as amino-modified MIL-53 (Al), MIL-101 (Al), CAU-1 (Al), or amino-modified Al2O3 nanoparticles; water-based polysiloxane refers to water-soluble polysiloxane formed by hydrolysis, cross-linking and polymerization of various silanes, referred to as POS.

[0005] In order to achieve the above object, the present invention provides a method for preparing an Al-MOF / polysiloxane composite sizing agent for basalt fiber, which specifically comprises the following steps:

[0006] Step 1: Preparation of Al-MOF nanoparticles

[0007] (1) mixing an aluminum salt solution and an amino organic ligand solution together, adding the mixed solution into a hydrothermal reaction kettle, and performing a hydrothermal reaction in an oven;

[0008] (2) cooling the sample obtained in step (1) to room temperature, centrifuging, washing, and drying to obtain Al-MOF nanoparticles;

[0009] Step 2: Preparation of Al-MOF / polysiloxane composite impregnant

[0010] (1) using ethanol aqueous solution as a solvent, adding the Al-MOF nanoparticles in step 1, and ultrasonically dispersing to obtain an Al-MOF suspension;

[0011] (2) Adding aqueous polysiloxane solution to the Al-MOF suspension and performing ultrasonic dispersion to obtain an Al-MOF / polysiloxane composite impregnating agent for basalt fiber.

[0012] The preparation method of the water-soluble polysiloxane (POS) of the present invention is:

[0013] (1) At room temperature, two raw materials are added into a beaker and mixed evenly; the two raw materials are both alkoxysilanes or both aminoalkoxysilanes or one alkoxysilane and one aminosiloxane; the molar ratio of the two raw materials is 1:1;

[0014] (2) Slowly add a certain amount of deionized water or distilled water as an initiator into the beaker under continuous stirring to initiate the polymerization reaction;

[0015] (3) After the polymerization reaction has occurred for a certain period of time, hexamethyldisiloxane (HMDS) is added to the beaker as a terminator to terminate the polymerization reaction, and a clear and transparent aqueous product is obtained, which is a water-soluble polysiloxane solution.

[0016] The mass concentration of the aqueous polysiloxane solution in the composite wetting agent of the present invention is 1.0-2.5%. Preferably, the mass concentration of the aqueous polysiloxane solution in the composite wetting agent is 1.5%.

[0017] The hydrothermal reaction temperature of step 1 of the present invention is 120-150° C. and the reaction time is 24-48 hours.

[0018] The aluminum salt of the present invention is aluminum chloride (III) hexahydrate, aluminum carbonate, aluminum nitrate or aluminum sulfate; the aluminum salt solution is obtained by dissolving the aluminum salt in deionized water; the mass volume ratio of the aluminum salt to the deionized water is 0.76-1.0g:15mL.

[0019] The amino organic ligand solution of the present invention is obtained by dissolving an amino organic ligand in N, N-dimethylformamide, and the mass volume ratio of the amino organic ligand to N, N-dimethylformamide is 0.56-1.0 g:15 mL; the amino organic ligand is 2-aminoterephthalic acid, 3-amino-1,2,4-triazole, 3-amino-1,2,4-triazole, 5-aminotetrazolyl, 5-(5-aminotetrazolyl)-1,3-phthalic acid, 3-amino-4-(pyridin-4-yl)benzoic acid, 5-amino-1H-imidazole-4-carbonitrile or 2-amino-1,3,5-benzenetricarboxylic acid, 2-aminobenzimidazole.

[0020] The aluminum salt solution of the present invention is mixed with the 2-aminoterephthalic acid solution in a volume ratio of 1:1.

[0021] The method for using the sizing agent of the present invention, i.e., the sizing method, is specifically as follows:

[0022] (1) The commercial basalt fiber was soaked in acetone, ultrasonically dispersed and de-slurried for 3 hours, and then dried in an oven at 80° C. for 24 hours for use.

[0023] (2) The basalt fiber bare wire after thorough desizing treatment is immersed in the above-mentioned Al-MOF / POS composite impregnating agent for 5-10 minutes for sizing treatment, and then placed in an oven for drying for 20-30 minutes to complete the sizing process.

[0024] The present invention also provides an Al-MOF / polysiloxane composite sizing agent specially used for basalt fiber prepared by the preparation method, wherein the main components of the composite sizing agent are water-based polysiloxane and Al-MOF nanoparticles.

[0025] The sizing agent of the present invention is mainly composed of partially cross-linked silicone polymer-waterborne polysiloxane, which is composited with metal organic framework Al-MOF nanoparticles, contains silicon (Si), aluminum (Al) and oxygen (O) elements, simulates the main components of basalt fiber, is coated on the surface of basalt fiber to form a topological structure, and forms a variety of interaction forces with the surface of basalt fiber, including covalent bonds, hydrogen bonds, electrostatic interactions, cation-π bonds, anion-π bonds, intermolecular forces, etc. After the basalt fiber is sized with the composite sizing agent of the present invention, on the one hand, the tensile breaking stress and rupture modulus of the fiber can be maintained at more than 95% at 250°C, and the strength can be maintained at more than 85% at 400°C, which significantly improves the thermomechanical properties of the basalt fiber; on the other hand, the polar hydroxyl groups and non-polar alkane segments of the partially cross-linked polysiloxane are self-assembled on the fiber surface under the influence of the fiber surface and Al-MOF, and the micro-nano structure formed by Al-MOF synergistically improves the surface wetting properties of the basalt fiber. The dynamic contact angle measures the water contact angle to be 140.1±0.6°, and the diiodomethane contact angle to be 111.2±0.9°, achieving the hydrophobic and oleophobic dual-fouling and waterproof properties of the basalt fiber. The Al-MOF / polysiloxane composite sizing agent of the present invention provides a guarantee for the heat resistance, antifouling and waterproof properties of basalt fiber and its textiles.

[0026] Compared with the prior art, the composite sizing agent prepared by the present invention significantly improves the thermomechanical properties and wetting properties of basalt fiber. The preparation method has scientific principles, is easy to operate, highly efficient, low cost, has few components, and has a simple sizing process. After the basalt fiber is sizing-treated with the sizing agent, a topological structure of basalt-like components is constructed on the surface of the basalt fiber, giving the fiber excellent thermomechanical properties and surface amphiphobic properties, realizing the high temperature resistance and anti-fouling and waterproof self-cleaning functions of textile basalt fiber in the field of special-purpose clothing and thermal filtration devices, and having great application potential, providing a guarantee for the heat resistance, anti-fouling and waterproof properties of basalt fiber and its textiles. It is suitable for large-scale promotion. Description of the drawings:

[0027] Figure 1 The present invention is a schematic diagram of the preparation and sizing process of the Al-MOF / polysiloxane composite impregnating agent.

[0028] Figure 2 This is the infrared spectra of POS, Al-MOF and composite wetting agent Al-MOF / POS prepared in Example 1 of the present invention.

[0029] Figure 3 This is a thermogravimetric curve of the Al-MOF / polysiloxane composite impregnant prepared in Example 1 of the present invention.

[0030] Figure 4This is an infrared spectrum of the basalt fiber sizing treated with the composite sizing agent of Examples 1-4 according to the present invention.

[0031] Figure 5 The SEM images of the surface of the basalt fiber treated with a composite impregnating agent involved in the present invention are shown in FIG. 1 , wherein a is BF; b is BF-POS; c is BF-Al-MOF / POS-1.0%; d is BF-Al-MOF / POS-1.5%; e is BF-Al-MOF / POS-2.0%; and f is BF-Al-MOF / POS-2.5%.

[0032] Figure 6 This is a graph showing the breaking stress test results at different temperatures for the basalt fiber treated with a composite sizing agent according to the present invention.

[0033] Figure 7 The present invention is a graph showing the elongation at break test results at different temperatures for basalt fibers treated with a composite sizing agent.

[0034] Figure 8 The polar and non-polar contact angle images of the basalt fiber monofilament sizing treated with the composite sizing agent of Example 1 of the present invention are shown in FIG. a is the non-polar contact angle (diiodomethane); and b is the polar contact angle (water). Specific implementation method:

[0035] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in combination with experimental data and implementation examples.

[0036] Evaluation of the strengthening effect of the wetting agent prepared in the present invention:

[0037] The thermodynamic performance simulation device was used to evaluate the enhancement effect of the sizing agent on the thermodynamic properties of basalt fiber. The experimental device consists of a tubular furnace heating device and a single fiber stretching device. The sizing fibers were grouped and treated in a tubular furnace at 100℃, 150℃, 200℃, 250℃, 300℃, and 400℃ for 30 minutes, and then the single fiber tensile performance test was performed to calculate the mechanical performance loss.

[0038] Embodiment 1:

[0039] This embodiment relates to a method for preparing an Al-MOF / polysiloxane composite sizing agent for basalt fiber, comprising the following steps:

[0040] Step 1: Preparation of Al-MOF

[0041] (1) 0.76 g of AlCl3·6H2O was dissolved in 15 mL of deionized water, and 0.56 g of 2-aminoterephthalic acid (NH2-BDC) was dissolved in 15 mL of DMF; the two different solutions were then quickly mixed together, and the mixture was introduced into a 100 mL steel hydrothermal reactor lined with polytetrafluoroethylene, and placed in an oven at 150° C. under static conditions for 24 hours; the molar ratio of AlCl3·6H2O to NH2-BDC was 1:1;

[0042] (2) cooling the sample obtained in step (1) to room temperature, centrifuging to obtain a light yellow solid product, and washing with anhydrous methanol; repeatedly centrifuging all samples, and finally drying in a vacuum oven at 60° C. overnight to obtain an amino MIL-53 (Al) metal organic framework material, i.e., Al-MOF nanoparticles;

[0043] Step 2: Preparation of waterborne polysiloxane

[0044] (1) At room temperature, 4.98 mL of methyltriethoxysilane (MTES) and 5.85 mL of 3-aminopropyltriethoxysilane (KH-550) (MTES:KH-550 molar ratio 1:1) were added to a beaker, and then stirred at 750 rpm for 15 min using a magnetic stirrer;

[0045] (2) Keeping the magnetic stirring rate constant, slowly add 20 mL of deionized water (or distilled water) into the beaker as an initiator to start the polymerization reaction;

[0046] (3) 30 minutes after the polymerization reaction, 0.52 mL of hexamethyldisiloxane (HMDS) was added to the beaker as a terminator to terminate the polymerization reaction, and a clear and transparent aqueous product was obtained, which was an aqueous polysiloxane solution;

[0047] Step 3: Preparation of the infiltrant

[0048] (1) 150 mL of deionized water and 150 mL of anhydrous ethanol were mixed as a solvent, 0.3 g of the Al-MOF nanoparticles prepared in step 1 were added, and ultrasonic dispersion was performed; then 13.5 mL of the aqueous polysiloxane prepared in step 2 was added, and ultrasonic dispersion was performed to prepare an Al-MOF / polysiloxane composite impregnating agent for basalt fiber having a weight percentage concentration of 1.5% of aqueous polysiloxane, which was recorded as Al-MOF / POS-1.5%, and the mixture was sealed and stored.

[0049] In this example, the composite impregnant Al-MOF / POS-1.5% was characterized by Fourier transform infrared spectrum and compared with POS and Al-MOF. The results are as follows: Figure 2 shown.

[0050] from Figure 2 It can be seen that 3375cm -1 The absorption bands at 2861 and 2925 cm are attributed to the stretching vibration of Si-OH bonds. -1 The peak between 1270cm and 1270cm corresponds to the asymmetric stretching vibration of the -CH2 group. -1 The peak at 915-994cm is related to the bending vibration of the -OH group. -1 The broad bands in the range are related to Si-O and Si-C bonds and are attributed to the stretching modes of the siloxane bridges that form the silica network. -1 There is an obvious absorption peak at , which belongs to the Si-N bond, symbolizing the combination of POS and the amino group on Al-MOF.

[0051] In this example, a synchronous thermal analyzer was used to perform a thermogravimetric curve test on the prepared Al-MOF / POS-1.5%. The results are shown in Figure 3 As shown. Figure 3 It can be seen from the images of Al-MOF / POS-TG and Al-MOF / POS-DTG in the figure that the decomposition temperature of the composite impregnant prepared in Example 1 is 450°C, and it has good temperature resistance.

[0052] Embodiment 2:

[0053] The present embodiment relates to a method for preparing an Al-MOFs / polysiloxane composite wetting agent for basalt fiber. The difference from Example 1 is that the amount of aqueous polysiloxane added in step 3 is 9 mL, and the other steps are the same as Example 1. An Al-MOF / polysiloxane composite wetting agent for basalt fiber with a weight percentage concentration of 1.0% of aqueous polysiloxane is prepared, which is recorded as Al-MOF / POS-1.0%.

[0054] Embodiment 3:

[0055] The present embodiment relates to a method for preparing an Al-MOF / polysiloxane composite wetting agent for basalt fiber. The difference from Example 1 is that the amount of aqueous polysiloxane added in step 3 is 18 mL, and the other steps are the same as Example 1. An Al-MOF / polysiloxane composite wetting agent for basalt fiber with a weight percentage concentration of 2.0% of aqueous polysiloxane is prepared, which is recorded as Al-MOF / POS-2.0%.

[0056] Embodiment 4:

[0057] The present embodiment relates to a method for preparing an Al-MOFs / polysiloxane composite wetting agent for basalt fiber. The difference from Example 1 is that the amount of aqueous polysiloxane added in step three is 22.5 mL, and the other steps are the same as Example 1. An Al-MOF / polysiloxane composite wetting agent for basalt fiber with a weight percentage concentration of aqueous polysiloxane of 2.5% is prepared, which is recorded as Al-MOF / POS-2.5%.

[0058] Embodiment 5:

[0059] This example involves a performance test experiment of the composite sizing agent prepared in Examples 1-4. The composite sizing agent is used to perform sizing treatment on basalt fibers. The infrared spectrum, microscopic morphology SEM characterization, thermomechanical properties and surface contact angle of the sized basalt fibers are tested. The results are as follows: Figure 4-Figure 8 shown.

[0060] The specific sizing treatment method is:

[0061] (1) soaking commercial basalt fiber in acetone, ultrasonically dispersing and desizing for 3 hours, and then drying in an oven at 80° C. for 24 hours for later use;

[0062] (2) The basalt fiber bare wires after thorough desizing treatment are immersed in the composite sizing agent of Examples 1-4 for 5-10 minutes respectively for sizing treatment, and then placed in an oven for drying treatment at 100-120° C. for 20-30 minutes to complete the sizing process.

[0063] The BF-POS-1.5%, BF-Al-MOF / POS-1.0%, BF-Al-MOF / POS-1.5%, BF-Al-MOF / POS-2.0%, and BF-Al-MOF / POS-2.5% described in this embodiment represent the basalt fibers after untreated basalt fibers (BF) are sized with sizing agents POS-1.5%, Al-MOF / POS-1.0%, Al-MOF / POS-1.5%, Al-MOF / POS-2.0%, and Al-MOF / POS-2.5%, respectively.

[0064] The preparation method of the impregnating agent POS-1.5% is different from that of Example 1 in that no Al-MOF nanoparticles are added in step (3).

[0065] from Figure 4 From the Fourier transform infrared spectrum, we can see that 769cm -1 and 691cm -1 The peaks at 1400-1700cm are related to the symmetric stretching mode and bending mode of Si-O-Si bonds, which also verifies the successful slurrying of polysiloxane. -1The vibration bands in the range belong to Al-MOF, proving its effective sizing on BF. The FTIR curves of BF-Al-MOF / POS-1.0%, BF-Al-MOF / POS-1.5%, BF-Al-MOF / POS-2.0% and BF-Al-MOF / POS-2.5% are very similar to the FTIR curves of BF, which also shows that the composite impregnant does build a topological structure with similar composition to BF after sizing BF, which is conducive to the close combination of the two.

[0066] from Figure 5 It can be seen from the SEM characterization that the sizing agents prepared in Examples 1-4 can form a uniform and dense film on the surface of basalt fiber, and with the increase of POS concentration, the roughness of the fiber surface increases, but it does not increase monotonically. This shows that the increase of POS concentration is conducive to the effective adhesion of Al-MOF particles on the BF surface and the close combination with POS to form a composite film.

[0067] In this example, BF, BF-POS-1.5%, BF-Al-MOF / POS-1.0%, BF-Al-MOF / POS-1.5%, BF-Al-MOF / POS-2.0% and BF-Al-MOF / POS-2.5% were tested for thermodynamic properties. The results are as follows: Figure 6 and Figure 7 As shown. Figure 6From the fracture stress test results at different temperatures, it can be seen that the fracture forces of BF at 25°C, 100°C, 150°C, 200°C, 300°C and 400°C are 8.04, 7.26, 7.14, 7.74, 4.2, 3.4 and 3.5 cN, respectively. In other words, compared with BF at 25°C, the fracture forces of BF at 200°C, 250°C, 300°C and 400°C are reduced by 96.3%, 52.2%, 42.3% and 43.5%, respectively. When the heat treatment temperature is higher than 250°C, the fracture force of BF drops sharply. The breaking force values ​​of BF-POS-1.5%, BF-Al-MOF / POS-1.0%, BF-Al-MOF / POS-1.5%, BF-Al-MOF / POS-2.0% and BF-Al-MOF / POS-2.5% without heat treatment were 11.8, 12.6, 18.5, 17.6 and 15.0, respectively, which were 46.77%, 56.72%, 130.01%, 118.91% and 86.57% higher than those of BF, respectively. The breaking forces after treatment at 200°C were 13.0, 12.7, 21.1, 18.3 and 16.0 cN, respectively, which were slightly higher than those of the samples without heat treatment, proving that POS improved the adhesion between the wetting agent and the fiber, thereby increasing the breaking force. The breaking forces of BF-POS-1.5%, BF-Al-MOF / POS-1.0%, BF-Al-MOF / POS-1.5%, BF-Al-MOF / POS-2.0% and BF-Al-MOF / POS-2.5% treated at 250°C were 9.0, 9.8, 18.0, 14.1 and 11.1 cN, respectively, which were reduced to 76.27%, 77.78%, 97.30%, 80.11% and 74.00% of the original values ​​compared with the samples without heat treatment. The breaking forces of BF-POS-1.5%, BF-Al-MOF / POS-1.0%, BF-Al-MOF / POS-1.5%, BF-Al-MOF / POS-2.0% and BF-Al-MOF / POS-2.5% treated at 400°C were 6.3, 7.0, 15.8, 12.2 and 10.3 cN, respectively, which were reduced to 53.39%, 55.56%, 85.41%, 69.32% and 68.67% of the original values, respectively, compared with the samples without heat treatment. However, for the BF-Al-MOF / POS-1.5% sized in Example 1, the fiber can still maintain more than 85% of the mechanical properties even after heat treatment at 400°C.

[0068] from Figure 7From the test results of elongation at break at different temperatures, it can be seen that the elongation at break of BF without heat treatment is 1.58%. After heat treatment at 200℃, 250℃ and 400℃, the values ​​dropped to 1.32%, 0.99% and 0.90%, respectively. The elongation at break of the BF-POS-1.5% sample increased to 2.06% at room temperature, and remained at 1.63% and 1.65% at 250℃ and 400℃, respectively, with almost no further decrease. This result shows that the organopolysiloxane layer can provide flexibility and toughness to the fiber, thereby preventing the fiber from becoming brittle. At the same time, with the increase of NH2-MIL-53(Al) content, the elongation at break of the fiber was also significantly improved. The best performing sample is BF-Al-MOF / POS-1.5%, with elongations at break of 2.56%, 2.6%, 2.64%, 2.34%, 2.21%, 2.04% and 2.02% at 25℃, 100℃, 150℃, 200℃, 250℃, 300℃ and 400℃, respectively. At room temperature, the elongation at break increased by up to 162% compared with the untreated basalt fiber (BF); at 300℃, the elongation at break remained at 79.69% at room temperature.

[0069] In this example, contact angle tests were performed on BF, BF-POS-1.5% and BF-Al-MOF / POS-1.5% (Example 1). Single fibers were placed on the surfaces of diiodomethane and water, and the contact angles of the fiber surfaces were tested. The results are shown in FIG. Figure 6 And as shown in Table 1.

[0070] Table 1 Dynamic contact angle data

[0071]

[0072] from Figure 8 It can be seen from Table 1 that the composite wetting agent prepared in Example 1 can form a uniform and dense film on the surface of the basalt fiber, so that the polar and non-polar contact angles of the basalt fiber surface can reach 140.1±0.6° and 111.2±0.9°, respectively, giving the basalt fiber surface a dual hydrophobic (hydrophobic and oleophobic) property, and realizing the anti-fouling and waterproof function of the basalt fiber.

[0073] These data highlight the effectiveness of multiple binding forces in maintaining the integrity of the sizing agent coating and fiber, especially under high temperature conditions. Among them, the composite sizing agent prepared in Example 1 has the best effect. It is worth noting that with the increase of the concentration of polysiloxane in the sizing agent, the breaking force and elongation at break are both on a downward trend after growing to a certain extent. This is because there are too many polysiloxane macromolecules in the sizing agent, which will cause a larger amount of infiltration and adsorption on the fiber surface, resulting in differences in the sizing thickness on the fiber surface due to polymer self-aggregation, which will lead to uneven stress when the fiber is stressed, and as the proportion of polymer increases, the mechanical properties of the basalt fiber after sizing will decrease. At the same time, the excessive concentration of polysiloxane will also cause the overall sizing agent viscosity to increase with the volatilization of the solvent during the sizing process, causing Al-MOF to migrate difficultly, and it is easy to be fixed on the surface, and it is impossible to contact the fiber matrix and play its due role.

[0074] In summary, the composite wetting agent prepared in Example 1 can significantly improve the thermomechanical properties and wettability of basalt fibers. One sizing treatment can give basalt fibers dual functions, namely, thermomechanical stability at high temperatures and surface amphiphobicity, which can achieve long-term use performance of basalt fibers at high temperatures and surface anti-fouling and waterproof properties.

Claims

1. A method for preparing an Al-MOF / polysiloxane composite sizing agent for basalt fiber, characterized in that: The following steps are involved: Step 1: Preparation of Al-MOF nanoparticles (1) mixing an aluminum salt solution and an amino organic ligand solution and adding them into a hydrothermal reaction kettle to perform a hydrothermal reaction in an oven; (2) cooling the sample obtained in step (1) to room temperature, centrifuging, washing, and drying to obtain Al-MOF nanoparticles; Step 2: Preparation of Al-MOF / polysiloxane composite impregnant (1) using ethanol aqueous solution as a solvent, adding the Al-MOF nanoparticles in step 1, and ultrasonically dispersing to obtain an Al-MOF suspension; (2) Adding aqueous polysiloxane solution to the Al-MOF suspension and performing ultrasonic dispersion to obtain an Al-MOF / polysiloxane composite impregnating agent for basalt fiber.

2. The method for preparing the Al-MOF / polysiloxane composite sizing agent for basalt fiber according to claim 1, characterized in that: The preparation method of the water-soluble polysiloxane is: (1) At room temperature, two raw materials are added into a beaker and mixed evenly; the two raw materials are both alkoxysilanes or both aminoalkoxysilanes or one alkoxysilane and one aminosiloxane; (2) Deionized water or distilled water is added dropwise to the beaker as an initiator under continuous stirring to initiate a polymerization reaction; hexamethyldisiloxane is then added to terminate the polymerization reaction to obtain a clear and transparent aqueous product, namely, a water-soluble polysiloxane solution.

3. The method for preparing the Al-MOF / polysiloxane composite sizing agent for basalt fiber according to claim 1, characterized in that: The mass concentration of the aqueous polysiloxane solution in the composite impregnating agent is 1.0-2.5%; the ethanol aqueous solution is prepared by mixing deionized water and anhydrous ethanol in a volume ratio of 1:

1.

4. The method for preparing the Al-MOF / polysiloxane composite sizing agent for basalt fiber according to claim 1, characterized in that: The mass concentration of the aqueous polysiloxane solution in the composite wetting agent is 1.5%.

5. The method for preparing the Al-MOF / polysiloxane composite sizing agent for basalt fiber according to claim 1, characterized in that: The hydrothermal reaction temperature of step 1 is 120°C-150°C, and the reaction time is 24-48h.

6. The method for preparing the Al-MOF / polysiloxane composite sizing agent for basalt fiber according to claim 1, characterized in that: The aluminum salt is aluminum chloride (III) hexahydrate, aluminum carbonate, aluminum nitrate or aluminum sulfate; the aluminum salt solution is obtained by dissolving the aluminum salt in deionized water; the mass volume ratio of the aluminum salt to the deionized water is 0.76-1.0 g:15 mL.

7. The method for preparing the Al-MOF / polysiloxane composite sizing agent for basalt fiber according to claim 1, characterized in that: The amino organic ligand solution is obtained by dissolving an amino organic ligand in N,N-dimethylformamide, and the mass volume ratio of the amino organic ligand to N,N-dimethylformamide is 0.56-1.0 g:15 mL; the amino organic ligand is 2-aminoterephthalic acid, 3-amino-1,2,4-triazole, 3-amino-1,2,4-triazole, 5-aminotetrazolyl, 5-(5-aminotetrazolyl)-1,3-benzenedicarboxylic acid, 3-amino-4-(pyridin-4-yl)benzoic acid, 5-amino-1H-imidazole-4-carbonitrile or 2-amino-1,3,5-benzenetricarboxylic acid, 2-aminobenzimidazole.

8. The method for preparing the Al-MOF / polysiloxane composite sizing agent for basalt fiber according to claim 1, characterized in that: The aluminum salt solution and the 2-aminoterephthalic acid solution are mixed in a volume ratio of 1:

1.

9. The method for preparing the Al-MOF / polysiloxane composite sizing agent for basalt fiber according to claim 2, characterized in that: The molar ratio of the two raw materials is 1:

1.

10. The Al-MOF / polysiloxane composite sizing agent for basalt fiber prepared by the preparation method of claim 1, characterized in that: The main components of the composite wetting agent are water-based polysiloxane and Al-MOF nanoparticles; Al-MOF nanoparticles refer to amino-modified MIL-53 (Al), MIL-101 (Al) or CAU-1 (Al) aluminum-based metal organic framework materials, or amino-modified Al2O3 nanoparticle metal organic framework materials; water-based polysiloxane refers to water-soluble polysiloxane formed by hydrolysis, cross-linking and polymerization of various silanes.

Citation Information

Patent Citations

  • Organic-inorganic hybrid film forming agent, microcapsule type high-temperature self-repairing basalt fiber water-based impregnating agent and preparation method of microcapsule type high-temperature self-repairing basalt fiber water-based impregnating agent

    CN111153608A

  • Enhanced basalt fiber impregnating compound and preparation method thereof

    CN113480199A

  • High-temperature-resistant basalt fiber composite material and preparation method thereof

    CN117659706A

Cited By

  • High-flame-retardant industrial equipment cable with excellent dynamic durability and preparation method of high-flame-retardant industrial equipment cable

    CN119541937A